The Implementation of Realistic Mathematics Education (RME) to Support Indonesian 5th-Grade Students to Learn Multiplication and Division - Nanang Setiadi (SEAMEO Regional Centre for QITEP in Mathematics, 2020)
This paper discusses the use of Realistic Mathematics Education (RME) as an alternative approach to enhance Indonesian 5th-grade students’ ability in the topics of multiplication and division. The study presents the analysis of Indonesian 5th-grade students’ difficulties in applying vertical multiplication and division, that is in reapplying the steps of the method. Furthermore, it describes a mathematics teaching learning practice to stimulate students in constructing their strategies, mathematical models, and number sense in solving mathematical problems that involve multiplication and division. In implementing RME, the steps taken to improve the learning process were: (1) analysing in detail the difficulties of students in vertical multiplication and division, (2) providing contexts of mathematical problems that can stimulate students to think mathematically, (3) holding a class mathematics congress, and (4) conducting a test to measure students’ achievement. The implementation of RME has helped the 5th-grade students to improve their ability in multiplication and division. There were more students whose grades passed the minimum passing score. Moreover, there was an increase in the class average test score.